Penerapan Metode Belajar Partisipatif dalam Meningkatkan Kemampuan Membaca Siswa di SDN 064960 Medan Polonia - Simanullang, Jodis; Fajar Utama Ritonga; Mia Aulina Lubis (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
In this era of increasingly rapid development and progress, there are so many learning resources and styles that can be applied by teaching staff to increase students' interest in learning and enthusiasm. However, even so, the current learning system still often finds cases where students will just sit listening to the teacher deliver learning material and only follow what is conveyed by the teacher without understanding what the teacher is conveying. Therefore, the teacher is expected to be able to foster students' interest in being directly involved in the learning process. Participatory learning can be interpreted as an effort by educators to involve students in learning activities. Participatory learning activities imply the participation of students in learning activities so that they can achieve the goals of the learning itself. The purpose of this study was to improve students' reading skills at UPT SDN 064960 using a participatory method. This activity is a field work practice in collaboration with campus programs teaching USU partners for approximately four months of assignment. The method used by researchers is a social work method at the mezzo intervention level with a groupwork approach. From the results of the implementation of participatory learning methods in improving students' reading skills, it was concluded that they could achieve predetermined goals in this program, namely increasing students' reading skills.